A review of legal frameworks for physically restraining and administering intramuscular medications for rapid tranquillisation to a person detained under Section 136 of the Mental Health Act 1983. (4th September 2014) - Kuloor, Chetan Bangra; Sethi, Faisil; Parsons, Andrew; O'Brien, Aileen; Sweeney, Caroline; Lepper, Robert; Johnston, Andy
Abstract: Section 136 of the Mental Health Act1983 is routinely used by the police to remove a person thought to be suffering from a mental disorder, from a place to which the public have access, to a place of safety. Persons detained under Section 136 of the Mental Health Act1983 routinely spend significant amounts of time in a place of safety whilst awaiting a mental health assessment. During that time it is feasible that the patient will require intramuscular medications for rapid tranquillisation, often with the use of physical restraint. However, Section 136 of the Mental Health Act1983 does not grant the power to treat a person against their will and there is a lack of clarity on the most appropriate legal framework for physically restraining and administering intramuscular medications for rapid tranquillisation to a person detained under Section 136 of the Mental Health Act1983 . In this article, we attempt to explore the various legal frameworks available and identify the one most appropriate for this purpose.